Research on the Impact of Continuing Medical Education on the Sustainable Development of Zhejiang Provincial Public Hospitals - Yin, Chang (Journal of Social Science and Humanities, 2026)
Objective: This paper explores the impact of continuing medical education (CME) in provincial hospitals on the sustainable development of public hospitals. Based on the KSA model (Knowledge, Skills, Attitudes), it analyzes the role of CME in optimizing the personnel structure of hospitals, improving the quality of talent cultivation, promoting discipline construction, and enhancing patient satisfaction. Methods: Taking the representative continuing medical education (CME) projects of provincial public hospitals in Zhejiang Province from 2013 to 2024 as the research objects, this paper analyzes the current situation of CME and then uses the KSA model to analyze the impact of CME on the sustainable development of public hospitals. Results: 95.7% of continuing medical education programs take the latest medical knowledge and technology as the core content, and the forms of these programs show a trend of diversification. Through knowledge updating and skill training, CME has significantly improved the professional level of medical staff in public hospitals, optimized the personnel structure, promoted talent cultivation and discipline construction, and also enhanced the satisfaction of both patients and medical staff. Conclusion: Continuing medical education in provincial hospitals plays a significant role in promoting the sustainable development of public hospitals. However, there is still room for improvement in humanistic medical education and practical skills training. Optimizing the blended teaching model, developing demand-oriented continuing medical education assessment, and improving information management are important directions for enhancing continuing medical education.